Where people look for online health information. (21st May 2016) - LaValley, Susan A.; Kiviniemi, Marc T.; Gage‐Bouchard, Elizabeth A.
Abstract: Objectives: To identify health‐related websites Americans are using, demographic characteristics associated with certain website type and how website type shapes users' online information seeking experiences. Methods: Data from the Health Information National Trends Survey 4 Cycle 1 were used. User‐identified websites were categorised into four types: government sponsored, commercially based, academically affiliated and search engines. Logistic regression analyses examined associations between users' sociodemographic characteristics and website type, and associations between website type and information search experience. Results: Respondents reported using: commercial websites (71.8%), followed by a search engines (11.6%), academically affiliated sites (11.1%) and government‐sponsored websites (5.5%). Older age was associated with the use of academic websites (OR 1.03, 95% CI 1.02, 1.04); younger age with commercial website use (OR 0.97, 95% CI 0.95, 0.98). Search engine use predicted increased levels of frustration, effort and concern over website information quality, while commercial website use predicted decreased levels of these same measures. Discussion: Health information seekers experience varying levels of frustration, effort and concern related to their online searching. Conclusion: There is a need for continued efforts by librarians and health care professionals to train seekers of online health information to select websites using established guidelines and quality criteria.